1986
DOI: 10.1063/1.337216
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of ultrathin SiO2 growth

Abstract: A new model for explaining the initial rapid oxidation of silicon in dry oxygen has been proposed. Creation of an oxygen-diffused zone near the Si-SiO2 interface is postulated. Our model takes into account the heretofore ignored phenomenon of diffusion of oxidizing species into the silicon substrate during initial exposure to such species. This occurs because of the low diffusion resistance offered by the ultrathin oxide films to the oxidizing species. The oxidizing species diffuses in such large amounts that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

1988
1988
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(5 citation statements)
references
References 18 publications
0
3
0
2
Order By: Relevance
“…This technique was subsequently used by Shettigar and Hughes (1972) the modelling of combustion of coke deposits in catalyst pellets. A somewhat more refined analysis, without the arbitrary assumption of linear profiles, has been carried out more recently by Murali and Murarka (1986) who have used this concept to explain the initial regime in the kinetics of silicon oxidation. However, an arbitrary thickness of the reaction zone is considered without any means of estimating its magnitude.…”
Section: Reaction Zonementioning
confidence: 98%
“…This technique was subsequently used by Shettigar and Hughes (1972) the modelling of combustion of coke deposits in catalyst pellets. A somewhat more refined analysis, without the arbitrary assumption of linear profiles, has been carried out more recently by Murali and Murarka (1986) who have used this concept to explain the initial regime in the kinetics of silicon oxidation. However, an arbitrary thickness of the reaction zone is considered without any means of estimating its magnitude.…”
Section: Reaction Zonementioning
confidence: 98%
“…However, as the oxide is thinner than 350 A, the model fails to ex-plain the anomalous initial rapid oxidation phenomenon. Much study (32)(33)(34)(35) has been done and various models have been proposed to explain and describe this phenomenon.…”
Section: Measurement Of the Refractive Indexes Of Ultrathin Ox-mentioning
confidence: 99%
“…However, there are claims by subsequent authors that this is not supported by experimental evidence and/or theoretical analyses . A number of investigators suggested that the oxidation reaction may not be localized at the SiO 2 ‐Si interface but is spread out over a region of finite thickness or even over the entire oxide layer . Other models replace the simple first‐order surface reaction kinetics with kinetics of increasing complexity.…”
Section: Introductionmentioning
confidence: 99%